Determine and Compare the Volume and Length of the Upper Airway Using Cone‑beam Computed Tomography Images in Patients with Obstructive Sleep Apnea - Molaei, Sona (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The disease is one of a variety of respiratory disorders during sleep. This disorder caused by the obstruction of the upper airways leads to a reduction in nighttime oxygenation and sleep disruption during the night. In this study, using cone-beam computed tomography (CBCT) images in patients with obstructive sleep apnea (OSA), we compared their airway volume and length with healthy people. Methodology: This descriptive cross-sectional study was carried out on CBCT scans of 50 patients (25 patients with OSA and 25 healthy subjects) who referred to the Department of Oral and Maxillofacial Radiology, School of Dentistry, Tabriz University of Medical Sciences. The data obtained from CBCT entered into the NNT viewer version 2.21 software. In this study, the mean area, mean volume, and total length of the upper airway were measured. The results of this study were conducted using SPSS version 17 software, and a significance level of P < 0.05 was considered. Results: The findings of this study revealed that the area and length of the upper airway were higher in patients with OSA than in healthy people, but the volume of airway in healthy subjects was higher than those with OSA. As well as, the vertical and horizontal length of soft palate was higher in people with OSA than in healthy people. The anteroposterior distance in patients with OSA was lower than normal subjects. Meanwhile, there was a difference between the vertical and horizontal length of the soft palate in healthy subjects and patients, both of which were statistically significant (P < 0.05). Conclusion: The final results of this study indicated that the area and length of the upper airway were higher in people with OSA than in healthy people, meaning that people with a longer upper airway have a higher risk of developing OSA.